A review of the direct and indirect effects of nitrogen on botrytis bunch rot in wine grapes - Mundy, D.C. (New Zealand Plant Protection, 2008)
Nitrogen is an important macronutrient for grapevines influencing a number of metabolic pathways and plant structures This review provides a summary of some direct and indirect effects of nitrogen fertilisation on bunch rot incidence in the field Direct changes due to increased nitrogen nutrition include greater thickness of the wax on berry surfaces and increased concentrations of the biochemical defence compounds produced in them Indirect changes that result from increased nitrogen include development of tighter bunches and denser canopies As integrated management systems become more complex a better understanding of different components such as nitrogen nutrition is required to allow vineyard managers to make informed decisions on how potential changes to current practices may influence disease and berry quality parameters